1997
DOI: 10.1159/000171619
|View full text |Cite
|
Sign up to set email alerts
|

Recent Developments in the Manometric Assessment of Upper Esophageal Sphincter Function and Dysfunction

Abstract: Coordinated application of videoradiography and solid-state manometry provides insight into the pathophysiology of oropharyngeal dysphagia and helps direct appropriate therapies for a variety of conditions causing this symptom. Controlled evaluations of various treatment modalities, however, are lacking and therapy often remains primarily empiric. Despite this limitation, important strides have been made in the overall management of these patients during the past decade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Whether the protective properties of the upper esophageal sphincter were overcome because of reflux‐induced transient relaxations or a defect function, such as a disturbed pharyngeal‐upper esophageal sphincter contractile reflex or an altered basal upper esophageal sphincter pressure, was not evaluated in the present study because the conventional water‐perfused system that was used was not optimal for that task. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Whether the protective properties of the upper esophageal sphincter were overcome because of reflux‐induced transient relaxations or a defect function, such as a disturbed pharyngeal‐upper esophageal sphincter contractile reflex or an altered basal upper esophageal sphincter pressure, was not evaluated in the present study because the conventional water‐perfused system that was used was not optimal for that task. 11 …”
Section: Discussionmentioning
confidence: 99%
“…Once the high-pressure zone of the UES was identified, the catheter was stabilized in the high-pressure zone for approximately 20 s and UES resting pressure was recorded. The catheter was then pulled back (i.e., moved superiorly) an additional 1–2 cm so that UES relaxation could be measured at the height of the swallow (i.e., to compensate for laryngeal elevation with swallowing), and the characteristic M-wave [21] was seen in the channel for sensor one. A posterior orientation of sensors two and three at the levels of the inferior constrictor and the base of the tongue, respectively, was obtained and assured via endoscopic visualization throughout data collection.…”
Section: Methodsmentioning
confidence: 99%
“…Study findings indicate that the characteristic spatial pressure distribution shown by earlier studies 1–6 was significantly altered by using a manometric catheter with a smaller diameter and configuration conforming to the UES anatomy in both young and elderly. In that, similar to prior studies 1–6 the round catheter assembly measured pressures that were significantly greater anteriorly and posteriorly compared with pressures recorded from lateral directions. This radial asymmetry was not present in the UES pressure profile when the smaller diameter conforming catheter assembly was used for measurement.…”
Section: Discussionmentioning
confidence: 71%
“…Radial asymmetry of the upper oesophageal sphincter high‐pressure zone (UESHPZ) is an accepted notion based on manometric studies profiling the resting pressure phenomenon within the UES 1–7 …”
Section: Introductionmentioning
confidence: 99%